Investor protection under unregulated financial reporting - Barton, Jan; Waymire, Gregory (Journal of Accounting and Economics, 2004)
We examine whether availability of higher quality financial information lessens investor losses during a period seen as a stock market crash. We focus on October 1929, which partly motivated sweeping financial reporting regulations in the 1930s. Using a sample of 540 common stocks traded on the New York Stock Exchange during October 1929, we find that the quality of firms’ financial reporting increases with managers’ incentives to supply higher quality financial information demanded by investors. Moreover, firms with higher quality financial reporting before October 1929 experienced smaller stock price declines during the market crash.